ECOLOGICALLY SAFE AND RESOURCE SAVING TECHNOLOGIES OF WATER PREPARATION - G. K. Feyziev; M. F. Jalilov; G. G. Guseynova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
New highly-efficient, ecologically safe and resource saving technologies of chemical desalination and softening of fresh and salt water are developed and proposed in the paper.